Nutrition competence of primary care physicians in Saudi Arabia: a cross-sectional study - Al-gassimi, Osamah (BMJ Open, 2020)
OBJECTIVES: Primary care physicians have an opportunity to support healthy dietary behaviours of patients by providing nutrition care. However, it is unclear whether primary care physicians in the Kingdom of Saudi Arabia (KSA) are sufficiently competent in nutrition. This study aimed to assess the nutrition competence of primary care physicians in KSA and identify whether nutrition competence is associated with the provision of nutrition care to patients living with diet-related chronic disease. DESIGN: A cross-sectional study. SETTING: Chronic disease clinics across 48 primary care centres under the Ministry of Health in the city of Jeddah, KSA. PARTICIPANTS: 90 primary care physicians completed the survey (response rate: 98%). General practitioners and family medicine residents, specialists, and consultants actively working in chronic disease clinics between February and May 2019 were included. PRIMARY AND SECONDARY OUTCOME MEASURES: Primary outcome measure was nutrition competence of primary care physicians measured via the validated nutrition competence (NUTCOMP) questionnaire. RESULTS: Primary care physicians perceived themselves as competent in nutrition care but their reported provision of nutrition care was limited. Confidence in their nutrition knowledge and skills elicited the lowest mean scores of 25.8 (±5.4) out of 35 and 29 (±5.2) out of 40, respectively. The reported provision of nutrition care was closely correlated with physicians’ confidence in their nutrition knowledge (r=0.57) and communication (r=0.52). Three factors were identified as predicting whether physicians provide nutrition care to patients: confidence in counselling about nutrition (p<0.001), having previous nutrition education (p=0.005) and a higher professional qualification (p=0.008). CONCLUSIONS: Primary care physicians felt confident in providing nutrition care to patients living with diet-related chronic disease. Primary care physicians would benefit from higher levels of nutrition knowledge and skills to effectively support patients to improve their dietary behaviours and health conditions, leading to a positive impact on public health.